Analysis of Social Forestry Policy in Increasing Forest Farmers' Income: Case Study in West Sumatra Province - Putra, Yozarwardi Usama; Frinaldri, Aldri; Lanin, Dasman; Rembrandt, Rembrandt (Institute of Computer Science (IOCS), 2024)
This study analyzes the implementation of social forestry policies in West Sumatra Province in an effort to increase the income of forest farmers. This study uses a quantitative method with a sample of 1,214 respondents from 10 Forest Management Units (KPH), this study shows the dominance of the Nagari Forest scheme (85.17%) which is in accordance with the local social structure. The characteristics of respondents are dominated by men (88%), generation X (50%), and have a high school/equivalent non-agricultural education. The results of the study showed an increase in forest farmers' income by 17.24% in 2023, exceeding the target of 5%, with an achievement of 344.80%. This success is supported by various government efforts, including socialization, capacity building, assistance with productive tools, facilitation of entrepreneurship, and product promotion. The social forestry policy in West Sumatra adapts national policies by considering the important role of the Minangkabau indigenous people in managing natural resources. The Nagari Forest scheme is the most appropriate for the social structure of the Minangkabau people. In the future, the government plans to expand the scope of the program, focus on developing forest product value chains, and integrating with village development programs. This study highlights the importance of policies that consider local contexts in improving community welfare and forest sustainability.